Necrotizing Enterocolitis After Open Cardiac Surgery for Congenital Heart Defects – A Serious Threat - Kargl, S.; Maier, R.; Gitter, R.; Pumberger, W. (Klinische Pädiatrie, 2013)
Neonates with congenital heart disease are at risk to develop necrotizing enterocolitis (NEC). Especially in the postoperative period after correction of a congenital heart defect this intestinal inflammatory disease can be a potentially life-threatening complication. The purpose of this case series is to define the specific features of NEC in the postoperative situation, with emphasis on diagnostic difficulties.Medical records of neonates developing severe NEC in the postoperative period after surgical correction of a congenital heart defect from 2008 to 2011 were reviewed and compared.7 neonates with NEC after surgical correction of a congenital heart defect were identified. In all 7 patients typical radiologic findings of NEC were missing. Diagnosis was late in all 7 cases; 5 patients already had intestinal perforation. In 3 patients NEC successfully managed before surgical correction of the congenital heart defect dramatically relapsed in the postoperative period. 2 patients showed intestinal mucormycosis, an entity not clearly differentiated from NEC. Due to progressed disease at diagnosis all patients required extensive surgical procedures; 2 of them subsequently died.In the postoperative situation after surgical correction of a congenital heart defect diagnosis of NEC might be challenging. The general condition of these children complicates clinical examination and characteristic radiologic signs are absent. Late diagnosis and exclusive pathogens cause high morbidity and mortality.
Keywords: nekrotisierende Enterokolitis; angeborene Herzfehler; Kinderherzchirurgie; intestinale Minderdurchblutung